2022
DOI: 10.1016/j.tranpol.2022.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the impact of an exogenous factor: An exponential smoothing model of the response of shipping to COVID-19

Abstract: Following the outbreak of the COVID-19 pandemic, various lockdown strategies restrained global economic growth bringing a significant decline in maritime transportation. However, the previous studies have not adequately recognized the specific impacts of COVID-19 on maritime transportation. In this study, a series of analyses of the Baltic Dry Index (BDI), the China Coastal Bulk Freight Index (CCBFI) and of container throughputs with and without the impact of COVID-19 were carried out to assess changing trends… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…In the next few months of 2020, it can be clearly found that the year-on-year growth rate is always negative from January 2020 to June 2020. It was inferred that the lockdown strategy had a negative influence on the economy and maritime trade, which in turn affected the container transportation sector ( Zhao et al, 2022 ). After June 2020, the Chinese government efficiently resumed work and production, the transportation industry gradually recovered in those four ports, and the year-on-year growth rate turned positive for the first time since the COVID-19 pandemic; the four ports showed resilience and vitality and the container traffic began to rebound.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the next few months of 2020, it can be clearly found that the year-on-year growth rate is always negative from January 2020 to June 2020. It was inferred that the lockdown strategy had a negative influence on the economy and maritime trade, which in turn affected the container transportation sector ( Zhao et al, 2022 ). After June 2020, the Chinese government efficiently resumed work and production, the transportation industry gradually recovered in those four ports, and the year-on-year growth rate turned positive for the first time since the COVID-19 pandemic; the four ports showed resilience and vitality and the container traffic began to rebound.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…According to Zhao et al (2022) , the prediction error can serve as an indicator to measure the impact of the COVID-19 pandemic on maritime transportation. The larger the error, the greater the impact of the COVID-19 pandemic on maritime transportation.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, they also found that lockdown in the behavioral changes was minimal, which suggested isolated differences between policies with and without lockdown. Readers can also refer to further studies about infectious spreading on various transportation systems at different scales, including studies by Muley et al ( 47 ), Kutela et al ( 48 ), Choi ( 49 ), Hu et al ( 50 ), Zhao et al ( 51 ), and Severo et al ( 52 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In contrast, other studies have analysed the influence of the pandemic on the vessel flow by treating time as a continuum. The exogenous effects on the shipping industry from the outbreak were studied using an exponential smoothing model ( Zhao et al, 2022 ), but it overlooked the fact that the progress of the pandemic varied with region. Xu et al (2021) analysed the effects of macroeconomy, disease severity, and governmental disease control measures on port operations using a panel regression model.…”
Section: Literature Reviewmentioning
confidence: 99%